2019
DOI: 10.3390/ijerph16071145
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarette Use and Smoking Initiation in Taiwan: Evidence from the First Prospective Study in Asia

Abstract: A growing literature indicates that electronic cigarette use increases the risk of subsequent initiation of conventional smoking among cigarette-naïve adolescents in several Western countries. This research assesses the same relationship in an Asian country, Taiwan. The Taiwan Adolescent to Adult Longitudinal Study is a school-based survey that was carried out in two waves in 2014 (baseline) and in 2016 (follow-up). It employs probability sampling to create nationally representative samples of students in juni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 42 publications
1
34
0
2
Order By: Relevance
“…The authors only cite a portion of these studies. In detail, young people have been recruited in the US and Canada 2-15 , UK [16][17][18] , Finland 19 , Mexico 20 , the Netherlands 21 , Romania 22 , Taiwan 23 , and Germany 24 . More than 100,000 young people have been recruited for these studies with observational periods of up to 24 months.…”
Section: Data Availabilitymentioning
confidence: 99%
“…The authors only cite a portion of these studies. In detail, young people have been recruited in the US and Canada 2-15 , UK [16][17][18] , Finland 19 , Mexico 20 , the Netherlands 21 , Romania 22 , Taiwan 23 , and Germany 24 . More than 100,000 young people have been recruited for these studies with observational periods of up to 24 months.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Since the time that we published our earlier analysis [8] and our paper on general considerations relating to vaping as a possible gateway into cigarette smoking [7] a number of other authors have presented evidence from prospective studies [9][10][11][12][13][14][15]. The studies vary in the extent to which potential confounding variables have been adjusted for, with large OR estimates tending to be reported in studies with more limited control.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a US study [14] ,which reported an OR of 6.8 (1.7-28.3), following adjustment for ten covariates independently associated with initiation of smoking, most of the other studies which appear to have better control for confounding gave lower estimates. These included a study in Taiwan [10] which reported an OR of 2.14 (1.66-2.75), a study in Germany [12] which reported an OR of 2.18 (1.65-2.87) and a study in Finland [11] which reported that adjustment reduced the OR from 11.52 (4.91-26.56) to 2.92 (1.09-7.85). Notably, a study in Great Britain [16] reported an OR of 11.89 (3.56-39.72) estimated using the usual logistic method, but a reduced value of 1.34 (1.05-1.72) using causal mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable uncertainty regarding the chemical constituents of the e-liquids delivered by the e-cigarettes in the studies included in the review. Where evidence on nicotine content was available, it indicated that a substantial majority of e-cigarettes in those studies delivered nicotine [22][23][24][25]. Many publications noted considerable uncertainty regarding nicotine content, including apparent mislabelling, and the need for greater clarity and reliability on this point.…”
Section: Study Selectionmentioning
confidence: 99%